Characterizations and growth of textured well-faceted ZnO films by low-pressure chemical vapor deposition on ITO glass substrates. (November 2017) - Tsai, Chin-Yi; Lai, Jyong-Di; Feng, Shih-Wei; Chen, Chien-Hsun; Yang, Fann-Wei; Wang, Hsiang-Chen; Tu, Li-Wei
Abstract: In this work, textured well-faceted ZnO films with 0.5 and 2.0 μm film thickness grown on indium tin oxide (ITO) glass substrates by low-pressure chemical vapor deposition (LPCVD) are analyzed by x-ray diffraction (XRD), scanning electron microscope (SEM), atomic force microscope (AFM), cathode-luminescence (CL), and transmittance measurements. The XRD results show that the 0.5 μm ZnO film grown on the ITO substrate almost equally presents ZnO(110) ridge-like and ZnO(100) polygon-like grain structures, while the 2.0 μm ZnO film particularly favors the growth of ZnO(110) ridge-like grain structures. These results could be explained by a possible model of the constraints of lattice-match between the ZnO and ITO unit cells. The XRD results also show that the average grain sizes of the 2.0 μm ZnO film are larger than those of the 0.5 μm ZnO film, while the strain of the 2.0 μm ZnO film is smaller than that of the 0.5 μm ZnO film. These XRD results are shown to strongly agree with the measurements from the SEM, AFM, CL, and transmittance as well. The results of this work provide information for the growth of textured well-faceted ZnO films on ITO glass substrates that could be potentially utilized for high-performance and low-cost transparent conductive oxides. Highlights: Textured well-faceted ZnO films with 0.5 and 2.0 μm film thickness are grown on indium tin oxide (ITO) glass substrates by low-pressure chemical vapor deposition (LPCVD). The 0.5 μm ZnO film presents ZnO(110) ridge-like and ZnO(100) polygon-like grain structures, while the 2.0 μm ZnO film favors ZnO(110) ridge-like one. The 2.0 μm ZnO film show a larger average grain size and a smaller strain. The results could be explained by the constraints of lattice-match between the ZnO and ITO unit cells.